2007
DOI: 10.1158/0008-5472.can-07-1515
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Integrated SV40 T/t-Antigen Cancer Signature in Aggressive Human Breast, Prostate, and Lung Carcinomas with Poor Prognosis

Abstract: Understanding the genetic architecture of cancer pathways that distinguishes subsets of human cancer is critical to developing new therapies that better target tumors based on their molecular expression profiles. In this study, we identify an integrated gene signature from multiple transgenic models of epithelial cancers intrinsic to the functions of the Simian virus 40 T/t-antigens that is associated with the biological behavior and prognosis for several human epithelial tumors. This genetic signature, compos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
93
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 48 publications
10
93
0
Order By: Relevance
“…The targeted expression of the SV40 T/t-antigen led to the discovery of a conserved gene transcriptional signature in multiple epithelial tumors. 52 This genetic signature was found to be activated uniquely in tumors with aberrant p53, Rb or BRCA1 expression, and in breast, prostate and lung cancer, associated with an aggressive phenotype and poor prognosis, suggesting that they may represent rationale candidates for the preclinical testing of biologically important targets.…”
Section: Discussionmentioning
confidence: 97%
“…The targeted expression of the SV40 T/t-antigen led to the discovery of a conserved gene transcriptional signature in multiple epithelial tumors. 52 This genetic signature was found to be activated uniquely in tumors with aberrant p53, Rb or BRCA1 expression, and in breast, prostate and lung cancer, associated with an aggressive phenotype and poor prognosis, suggesting that they may represent rationale candidates for the preclinical testing of biologically important targets.…”
Section: Discussionmentioning
confidence: 97%
“…SV40 T/t antigens have been shown to be related to the biological behavior and prognosis of breast cancer (1)(2)(3). In this study, we successfully established SV40 T/t antigen-induced breast cancer transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although breast cancer is complex and highly variable in its clinical course, studies have indicated that SV40 T/t antigens are related to the biological behavior and prognosis of breast cancer (1)(2)(3). Previous studies have indicated that interleukins (IL1, IL2, IL12, IL15, IL18, IL24), tumor necrosis factor-α (TNF-α), and the interferon-γ (IFN-γ) can control the immune response and play an important role in breast cancer immunotherapy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, contrary to what is seen in normal murine cells (13), CDK2 activity appears essential for cell cycle progression when it is oncogenically driven by cyclin E and st expression (12). Because st is known to target pathways uniquely required for the transformation of human cells (14,15), tumor cells with altered pathways that mimic st/cyclin E expression could predictably be sensitive to selective inhibition of CDK2 activity.…”
mentioning
confidence: 97%